Safety issues with glucagon‐like peptide‐1 receptor agonists (pancreatitis, pancreatic cancer and cholelithiasis): Data from randomized controlled trials. Issue 9 (20th June 2017) - Monami, Matteo; Nreu, Besmir; Scatena, Alessia; Cresci, Barbara; Andreozzi, Francesco; Sesti, Giorgio; Mannucci, Edoardo
Abstract : Aim: Glucagon‐like peptide 1 receptor agonists (GLP1‐RA) have been associated with an increased risk of pancreatitis and pancreatic cancer. Prior meta‐analyses of randomized controlled trials failed to show any significant increase of risk; however, those meta‐analyses did not include the recently published cardiovascular outcome trials (CVOT) with GLP1‐RA, which provide a substantial additional body of data. The aim of the present meta‐analysis is to assess the effect of GLP1‐RA on pancreatitis, pancreatic cancers and cholelithiasis. Materials and methods: A Medline search for GLP‐1 receptor agonists (exenatide, liraglutide, lixisenatide, albiglutide, dulaglutide or semaglutide) was performed, collecting all randomized clinical trials with a duration >11 weeks, enrolling patients with type 2 diabetes and comparing a GLP‐1 receptor agonist with placebo or any other non‐GLP‐1 receptor agonist drug. Results: Of the 113 trials fulfilling inclusion criteria, 13 did not report information on pancreatitis, whereas 72 reported no events in all treatment groups. The incidence of pancreatitis and pancreatic cancer with GLP1‐RA was not significantly different from that observed in comparator arms (MH‐OR [95% CI] 0.93 [0.65‐1.34], P  = .71, and 0.94 [0.52‐1.70], P  = .84, respectively), whereas, a significantly increased risk of cholelithiasis (MH‐OR [95% CI] 1.30 [1.01‐1.68], P  = .041) was detected. Conclusions: Presently available data confirm the safety of GLP‐1 receptor agonists for pancreatitis. Conversely, therapy with those drugs is associated with an increased risk of cholelithiasis, which deserves further investigation.